2007
DOI: 10.1590/s0102-09352007000500030
|View full text |Cite
|
Sign up to set email alerts
|

The significance of cortisol on acclimation to salinity in pejerrey Odontesthes bonariensis

Abstract: The role of cortisol on the osmoregulation of pejerrey Odontesthes bonariensis at different salinities was investigated in adult fish injected with 0.7mg hydrocortisone per 100g body weight of fish, and transferred to 0, 5 and 20ppt of NaCl. Blood cortisol was 566ng/ml at the beginning of the experiment (0h) but surged to 1250ng/ml within 3h in cortisol-injected fish. Cortisol levels were influenced not only by treatment but also by time, being higher at 3h compared to 24h. Salinity level, time of exposure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…Similar to the present findings, significant rise in blood cortisol was also documented in the goldfish Carassius auratus exposed to increasing levels of salinity (Al-Khashali and Al-Shawi, 2013). Also, in pejerrey Odontesthes bonariensis it was shown that cortisol in blood rises in response to hyperosmotic salinity exposure magnitude and period (Tsuzuki et al, 2007). In the present study, the increased level of cortisol in treatment exposed to higher salinity is in agreement with the findings of several authors (Kammerer et al, 2010;Lim et al, 2005;Al-Khashali and Al-Shawi, 2013;Mancera et al, 1993) showing that the rise of cortisol level is a part of the overall physiological adaptation of fish exposed to saltwater.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the present findings, significant rise in blood cortisol was also documented in the goldfish Carassius auratus exposed to increasing levels of salinity (Al-Khashali and Al-Shawi, 2013). Also, in pejerrey Odontesthes bonariensis it was shown that cortisol in blood rises in response to hyperosmotic salinity exposure magnitude and period (Tsuzuki et al, 2007). In the present study, the increased level of cortisol in treatment exposed to higher salinity is in agreement with the findings of several authors (Kammerer et al, 2010;Lim et al, 2005;Al-Khashali and Al-Shawi, 2013;Mancera et al, 1993) showing that the rise of cortisol level is a part of the overall physiological adaptation of fish exposed to saltwater.…”
Section: Discussionsupporting
confidence: 93%
“…-ATPase activity in coho salmon, O. kisutch (McCormick and Bern 1989), sea trout, S. trutta L. (Madsen 1990a) and rainbow trout, O. mykiss (Madsen 1990b). However, Tsuzuki et al (2007) reported no benefit of single injection of cortisol in salt water tolerance in pejerrey, Odontesthes bonariensis. Abohegab and Hanke (1984) also reported single cortisol injection to carp, 3 h before salt water transfer, led to increase in cortisol, glucose and Na ?…”
Section: Discussionmentioning
confidence: 99%
“…This notion was only corrected when workers at Fisheries Experimental Stations in Japan, after much struggling to keep, transport and stock pejerrey in freshwater, realized the benefits of adding 3–5 psu (practical salinity units) of salt (NaCl) to the holding water. These empirical observations led to the studies of Tsuzuki et al (Tsuzuki, Aikawa, Strüssmann & Takashima 2000a, b; Tsuzuki, Ogawa, Strüssmann, Maita & Takashima 2000, 2007; Tsuzuki, Strüssmann & Takashima 2007), who demonstrated not only better survival and growth performance in brackish water but also the positive effects of salinity on ionic and osmoregulatory balance and mitigation of stress response (e.g. lowering of blood plasma cortisol level).…”
Section: Constraints To the Development Of Pejerrey Farming In South mentioning
confidence: 99%